2006
DOI: 10.1111/j.1365-2664.2006.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term demographic fluctuations in an orchid species driven by weather: implications for conservation planning

Abstract: Summary1. Management decisions are increasingly based on matrix models intended to predict the long-term fate of endangered species. However, certain elements of these models, such as life-state transition probabilities (vital rates), are difficult to parameterize and their values may vary depending on external conditions such as weather. Details of how weather might influence population performance are rare, yet necessary to assess the effects of global climate change on a species' distribution. 2. Based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 47 publications
8
62
0
1
Order By: Relevance
“…These results are in accordance with the previous findings on the variability in the inter-annual records of orchid numbers in northern Europe (Tamm 1991;Kindlmann and Balounova 1999;Oien and Moen 2002;Tali 2002;Brzosko 2003). Inter-annual fluctuations in orchid abundance are mainly induced by variations in climate, in particular temperature and rainfall (Wells et al 1998;Pfeifer et al 2006Pfeifer et al , 2011Pfeifer et al ). 2006Pfeifer et al and 2011 were the driest during the sampling period and the lowest number of individuals per species was recorded in 2011 at most of the study sites.…”
Section: Inter-annual Variability In Flowering At Community Levelsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with the previous findings on the variability in the inter-annual records of orchid numbers in northern Europe (Tamm 1991;Kindlmann and Balounova 1999;Oien and Moen 2002;Tali 2002;Brzosko 2003). Inter-annual fluctuations in orchid abundance are mainly induced by variations in climate, in particular temperature and rainfall (Wells et al 1998;Pfeifer et al 2006Pfeifer et al , 2011Pfeifer et al ). 2006Pfeifer et al and 2011 were the driest during the sampling period and the lowest number of individuals per species was recorded in 2011 at most of the study sites.…”
Section: Inter-annual Variability In Flowering At Community Levelsupporting
confidence: 92%
“…Stable microclimatic conditions, e.g. a warm winter or fresh summer, can favour population performance and avoid dormancy of flowering (Pfeifer et al 2006). The two factors antagonistically act in the case of grassland and woodland toward probability in flowering.…”
Section: Inter-annual Variability In Flowering In Different Habitatsmentioning
confidence: 99%
“…Kéry et al (2005) recommend multistate capturerecapture models after comparing methods to estimate survival rate. Pfeifer et al (2006) used matrix models to estimate longterm survival probabilities on the basis of rates of transition between life states. Tremblay et al (2009a) used a Bayesian capture-recapture multistate analysis for nine Australian Caladenia species to estimate dormancy and survival probabilities.…”
Section: Drakaea Isolatamentioning
confidence: 99%
“…Long-term measurements of fixed plots are the best approach to obtain population-size and -viability data for orchids. Pfeifer et al (2006) found that 4 years of data are usually adequate for modelling population size for terrestrial orchids, whereas longer periods of observation are better for studying population dynamics. Unfortunately, there are no annually repeated measurements of fixed plots for most of the rare orchids in WA and the existing population-size census data for these species is of limited use for assessing plant population size because of infrequent surveys, variations in sampling intensity and detectability problems (West Australian Auditor General 2009;Brundrett 2011).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…A few populations have also been subjected to unusually detailed studies of annual demographics (Carey, 1998(Carey, , 1999Heinrich, 2003;Pfeifer, 2004;Pfeifer et al, 2006a).…”
mentioning
confidence: 99%